Fostering future music teachers' professional skills: developing a signature pedagogy using e-learning - Karkina, Svetlana; Mena, Juanjo; Valeeva, Roza; Yarmakeev, Iskander; Dyganova, Elena; Bhullar, Mandeep (Frontiers in Education, 2023)
The emergency crisis due to the COVID-19 pandemic caused the noticeable changes, which stimulate the transition to the new normal based on the spreading of the digitalization. In this regard the revision of the learning tools in higher education exposes the new challenges requires development and implementation digital technologies. Fostering future music teacher` professional skills needs in designing of the online resources that provide the close student-teacher interaction, as well as engagement of students and regulation of their professional music practice. The investigation of the efficiency of using e-learning for training future music teacher` professional skills was carried out in the paper. To improve future music teacher` skills according to the features of the professional field the signature pedagogy approach was suggested. Based on the theory of Shulman the signature pedagogy in music education was developed and implemented in e-learning environment by the small private online course. The aim of the research was stated: How and which students’ music teacher professional skills are affected in the process of online learning based on the signature approach? The research was conducted at Kazan Federal University. During the educational process students studied the the professional practicum. Totally 124 students from 1st to 4st courses had taken part in the experimental work in the 2021-2022 academic year. All of them studied the bachelor programs for future music teacher as full- or part-time regime. During the experiment they had been learning the online course in MOODLE. The complex of online tasks which cover all the types of the music teacher` professional activities was suggested. Considering the aim of the research, the multi-case study research methodology was chosen, using a mixed method approach, resourcing mainly to questionnaire, interview, documental analysis, and observation as data gathering methods, and descriptive statistical analysis, as data analysis techniques. The main results demonstrate the effectiveness of the developed online course that allowed to significantly foster students’ music teacher professional skills. The contribution of the paper brings the detail characteristic of the signature pedagogy in music education, and the way of its implementation by the means of online tools.